Expert consensus on gamification strategies for ICT courses in higher education: a modified Delphi approach - Jaramillo-Mediavilla, Lorena; Basantes-Andrade, Andrea; Casillas-Martín, Sonia; Cabezas-González, Marcos (Frontiers in Education, 2026)
Teaching Information and Communication Technologies (ICT) in higher education faces the challenge of engaging students accustomed to interactive and digital learning environments. Although gamification has emerged as a promising pedagogical strategy to enhance motivation, participation, and learning, there is still no consensus on which gamification elements and strategies should be prioritized in ICT courses. To address this gap, this study aimed to identify, through expert consensus, the most relevant gamification components for ICT teaching in higher education. A modified Delphi study with a mixed-methods design was conducted in two rounds: an open exploratory phase and a structured round using a five-point Likert scale. Twelve experts were selected based on a competence coefficient (K ≥ 0.75). Quantitative analyses included means, standard deviations, interquartile range (IQR), coefficient of variation (CV), and Kendall’s coefficient of concordance (W), complemented by qualitative thematic coding with an inter-coder reliability of κ = 0.82. Consensus thresholds followed current Delphi standards (≥ 80% agreement, IQR ≤ 1, CV ≤ 0.30, and W ≥ 0.60). The results indicate that experts prioritized challenges and quests (83% agreement; W = 0.66), followed by points and rewards (67%) and the complementary use of badges and leaderboards. Strong consensus was reached regarding the potential of gamification to strengthen problem-solving, critical thinking, and collaboration (100%; W = 0.90), and to increase active participation (100%) and promote deep understanding (83%). However, heterogeneity persisted in relation to the selection of technological platforms (W = 0.27) and specific strategies (W = 0.28), and the effects on academic performance were reported as inconsistent. Overall, the findings suggest that gamification is most effective when systematically integrated into ICT curricula, supported by teacher training and immediate feedback mechanisms. As no universal technological platform is recommended, the use of contextual selection criteria is essential. These results provide a conceptually validated reference framework for the design of gamified learning experiences in higher education and underscore the need for further empirical validation across diverse educational contexts.